Bridging the Gap between Accounting Academic Research and Practice: Some Conjectures from Romania - Catalin Nicolae Albu; Serban Toader (Journal of Accounting and Management Information Systems (JAMIS), 2012)
Answers have been sought to questions such as the following two for more than a decade: Why do accounting academics conduct research, and how important is this research to practice? This is not an easy task though. Academics' and practitioners' agendas, interests and approaches seem to be different, thus creating a gap between accounting academic research and practice. Various initiatives are intended to bridge this gap, to the benefit of academia, practice and students. Academics would integrate real-life data into their research and teaching, practitioners could find informed solutions to their immediate and future problems, and students would get a better understanding of the challenges and opportunities they will face in the future as professional accountants.
Keywords: M41; M40; 650; Accounting research; practice; bridging the gap